PENGARUH BUDAYA NUSANTARA TERHADAP IMPLEMENTASI NILAI-NILAI ISLAM DI INDONESIA - Dofari Dofari (IAIN Padangsidimpuan, 2018)
This article aims to find out Islamic values that can be easily implemented in Indonesia, convey the peculiarities of the realization of Islamic values in Indonesia, and their influence on the realization of Islamic cultural values. The method used to find out what will be used and distribute several books related to the topic of discussion in this article. This is where the values are very important to enable readers to be based on Islam by knowing the rights of certain customs to be preserved and furthermore not applying traditions that clearly deviate from Islam. The results of the discussion of this article are that the values of Islamic culture in Indonesia can be packaged so attractively when packing Islamic teachings with culture that people are not aware that the values of Islam have become a tradition in their daily lives